PENGARUH BRAND AWARENESS, BRAND LOYALTY, PERCEIVED QUALITY, BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (Studi Konsumen Sepeda Motor Matic Honda Scoopy Pada Dealer Honda Di Kota Banjarmasin - Akbar Ariadi; Meina Wulansari Yusniar; Ahmad Rifani (Universitas Lambung Mangkurat, 2019)
This research was aimed at examining and analyzing the effect of brand awareness, brand loyalty, perceived quality, brand image on the consumers’ purchasing decisions on the Honda Scoopy Matic Motorcycle at Honda Dealers in Banjarmasin. This research was conducted on the basis of used the quantitative approach, by using questionnaires distributed to 200 respondents; and the units of analysis were consumers who have purchased a Honda Scoopy Matic Motorcycle in Banjarmasin. Data were analyzed by the use of Structural Equation Model (SEM). The results of research showed that Brand Loyalty and Perceived Quality effected significantly to Consumers’ purchasing decisions, while Brand Awareness and Brand Image did not affect Consumers’purchasing decisions.